Seleksi Komposisi Medium Pertumbuhan dan Bahan Pembawa untuk Formulasi Cendawan Agens Hayati Fusarium oxysporum Non-Patogenik P21a - Fany Juliarti Panjaitan; Suryo Wiyono; Rahayu Widyastuti (The Indonesian Phytopathological Society (Perhimpunan Fitopatologi Indonesia), 2019)
Selection of Compositions of Growth Medium and Carriers for Formulation of Biological Agents of Non-Pathogenic Fusarium oxysporum P21aThe potency of non-pathogenic Fusarium oxysporum P21a (NPFo P21a) as a biological control agent has prospect to be developed commercially. The growth medium and carrier are the critical factor to formulate biological control. This study aimed to obtain the best solid medium dan lighting type for mycelium growth and sporulation as well as to determine the carrier and storage temperature which is suitable for NPFo P21a toward the survival of propagule and germination of shallot. The results showed that M2 medium treatment (rice grain:rice bran; 20:1 w/w) was the best medium for mycelium growth. The M3 medium treatment (20:2 w/w) was the best medium for sporulation of NPFo P21a. The near-UV lighting treatment was able to stimulate the macroconidium production of NPFo P21a. Talc-based formulation and the storage at 20 °C showed the best shelf-life for NPFo P21a with density of viable propagule and shallot germination better.